Krematorium s obřadní síní - Vižálek, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Diplomová práce řeší projektovou dokumentaci stavby krematoria s obřadní síní v městě Kuřim. Budova je situovaná u stávajícího hřbitova v okrajové části města. Návrh je koncipován jako moderní jednopodlažní (částečně dvoupodlažní) stavba rozčleněna na několik dílčích částí s různou výškovou úrovní střechy, přičemž obřadní síň vystupuje svou výškou nad celý objekt.

The thesis deals a project documentation of Crematorium with Ceremonial Hall in Kuřim. The building is located close to the existing cemetery on the outskirts of the city. The object is designed as a detached building, in the middle of building parcel. The proposal is conceived as a modern single-storey (partly two-storey) building divided into several sub-sections with different height levels of the roof and the Ceremonial Hall exceeds the height of the entire object.
Crematorium and ceremonial hall
Keywords: krematorium; obřadní síň; moderní; samostatně stojící; výškové úrovně; pultová střecha; plochá střecha; vazník; Crematorium; Ceremonial Hall; modern; detached; hight levels; shed roof; flat roof; truss